2012
DOI: 10.1111/clr.12049
|View full text |Cite
|
Sign up to set email alerts
|

Bifid mandibular canals and the factors associated with their presence: a medical computed tomography evaluation in a Taiwanese population

Abstract: Bifid canals were observed in 30.6% of subjects and 18.5% of hemi-mandibles. Significant association between length of bifid canals and gender, side of hemi-mandible, and cross-sectional bony area of mandible was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 19 publications
6
40
1
6
Order By: Relevance
“…Other classifications have been proposed by Nortjé et al 8 and Naitoh et al 13 The Langlais classification was chosen because it is still the most cited in the literature on bifurcation of the mandibular canal. 10,11 The most frequent mandibular canal bifurcation was Type I (72.7%), which is in agreement with the findings of other studies, 15,16 but our frequency percentage was higher. Rossi et al 11 reported a frequency of Type II mandibular canal bifurcation of 23.3%, which is close to our findings.…”
Section: A B C D Esupporting
confidence: 91%
See 2 more Smart Citations
“…Other classifications have been proposed by Nortjé et al 8 and Naitoh et al 13 The Langlais classification was chosen because it is still the most cited in the literature on bifurcation of the mandibular canal. 10,11 The most frequent mandibular canal bifurcation was Type I (72.7%), which is in agreement with the findings of other studies, 15,16 but our frequency percentage was higher. Rossi et al 11 reported a frequency of Type II mandibular canal bifurcation of 23.3%, which is close to our findings.…”
Section: A B C D Esupporting
confidence: 91%
“…However, the gender difference was not statistically significant. A recent study 15 found a higher prevalence of bifurcation in males, in the Taiwanese population. This study was carried out using medical CT.…”
Section: A B C D Ementioning
confidence: 86%
See 1 more Smart Citation
“…The only studies available describe the presence of BMCs on PANs without analysing potential influencing factors. Previous research conducted using various populations have described BMCs on multislice CT and CBCT, 3,[7][8][9][10][11][12][13] and have reported a wide variation in frequency, ranging from 10% 13 to 65%. 3 The present study is in line with Fu et al 10 who identified BMCs in 30.6% of patients and 18.5% of total hemimandibles, and Orhan et al 12 who observed BMCs in 27% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] The reported rate of bifid mandibular canals (BMCs) on PAN ranged from 0.08% to 8.30%, whereas on CBCT, it ranged from 10% to 66%. 3,[7][8][9][10][11][12][13] One type of BMC is the retromolar canal, which ends in the retromolar foramen (RF). CBCT studies 14,15 have reported rates of RF between 16% and 65%, 3,11,[13][14][15][16] similar to dry mandible studies ranging from 1.7% to 72.0%, [17][18][19] whereas PANs have yielded a lower range.…”
Section: Introductionmentioning
confidence: 99%